Vprašanje tragičnega v otroški literaturi - Vrečko, Janez (Otrok in knjiga, 1997)
A child meditates on the mythological way as long as the logical thinking of the world is not imposed to him/her. This is meant for him to be an important turn-over into the world of adults, from where there is no return to the precausal state in which only the "chosen" individuals, pushed to the verge ofa society, can persist. - In this sense Aristotle himself distinguishes two types of myths: in the first the events follow one another in a chronological order, in the second the events are mutually based in each other. One is the mythological circular time, an everlasting arrangement of events one after another; the other is the historic time where the events are mutually and causally connectes. This is the tragic time of an absolute subject, who everything she/he does, does knowingly and willingly. - Inside the mythological time "anagnorisis" and peripeteia possess the function which essentially contributes to a hero's death and resurrection, what can be done only from unhappiness towards happiness. When the myths exceed the character and its deed, the "anagnorisis" and peripeteia become the elements of character and thought, thus in the function of an appearing subject. They are linked to the positions where someone does something knowingly, something unknowingly and leaving off something willingly. - All these procedures are to a child's soul unknown, therefore tragic does not (yet) exist.
Keywords: children's literature; otroška književnost; mladinska književnost; young adult literature; tragično; literarne študije